Discovery of diverse polyomaviruses in bats and the evolutionary history of the Polyomaviridae - Tao, Ying (Microbiology Society, 2013)

(untitled) (J Gen Virol)
Polyomaviruses (PyVs) have been identified in a wide range of avian and mammalian species. However, little is known about their occurrence, genetic diversity and evolutionary history in bats, even though bats are important reservoirs for many emerging viral pathogens. This study screened 380 specimens from 35 bat species from Kenya and Guatemala for the presence of PyVs by semi-nested pan-PyV PCR assays. PyV DNA was detected in 24 of the 380 bat specimens. Phylogenetic analysis revealed that the bat PyV sequences formed 12 distinct lineages. Full-genome sequences were obtained for seven representative lineages and possessed similar genomic features to known PyVs. Strikingly, this evolutionary analysis revealed that the bat PyVs were paraphyletic, suggestive of multiple species jumps between bats and other mammalian species, such that the theory of virus–host co-divergence for mammalian PyVs as a whole could be rejected. In addition, evidence was found for strong heterogeneity in evolutionary rate and potential recombination in a number of PyV complete genomes, which complicates both phylogenetic analysis and virus classification. In summary, this study revealed that bats are important reservoirs of PyVs and that these viruses have a complex evolutionary history.